Classification of maternal thyroid function in early pregnancy using repeated blood samples. Issue 2 (2nd February 2022) - Knøsgaard, Louise; Andersen, Stig; Hansen, Annebirthe Bo; Vestergaard, Peter; Andersen, Stine Linding
Abstract : Objective: The assessment of maternal thyroid function in early pregnancy is debated. It is well-established that pregnancy-specific reference ranges preferably should be used. We speculated if the use of repeated blood samples drawn in early pregnancy would influence the classification of maternal thyroid function. Methods: Pregnant women with repeated early pregnancy blood samples were identified in the North Denmark Region Pregnancy Cohort. Each sample was used for the measurement of TSH, free T4 (fT4), thyroid peroxidase antibodies (TPO-Ab), and thyroglobulin antibodies (Tg-Ab) (ADVIA Centaur XPT, Siemens Healthineers). Method- and pregnancy week-specific reference ranges were used for the classification of maternal thyroid function. Results: Among 1466 pregnancies included, 89 women had TSH above the upper reference limit in the first sample (median pregnancy week 8) and 44 (49.4%) of these similarly had high TSH in the second sample (median week 10). A total of 47 women had TSH below the lower reference limit in the first sample and 19 (40.4%) of these similarly had low TSH in the second sample. Regarding women classified with isolated changes in fT4 in the first sample, less than 20% were similarly classified as such in the second sample. The percentage agreement between the samples was dependent on the level of TSH in the first sample and the presence of TPO- and Tg-Ab. Conclusion: In a large cohort of pregnant women, the classification of maternal thyroid function varied considerably with the use of repeated blood samples. Results emphasize a focus on the severity of thyroid function abnormalities in pregnant women.